Edukasi Manajemen Risiko Berbasis Teknologi Informasi untuk Peningkatan Kapasitas UMKM - Naqiya, Alfina Zsazsa; Amartiwi, Yasinta; Apriadi, Eko Aziz (CV. Tripe Konsultan, 2025)
This community service addresses the limited understanding of risk management and low digital literacy among Micro, Small, and Medium Enterprises (MSMEs) in Pulau Sebesi. The focus is on empowering business actors to strengthen their capacity in managing risks that threaten business continuity, particularly financial, operational, and market risks. The subject of this program is local MSME actors who are directly involved in daily business practices but still rely on conventional management methods. The purpose of the program is to improve participants’ ability to identify, analyze, and mitigate risks by integrating information technology into their business activities. A participatory approach was applied through training, group discussions, simulations, and mentoring, enabling MSME actors to actively engage in the learning process and apply knowledge directly into practice. The results showed a significant improvement in participants’ knowledge and skills in digital-based risk management. Behavioral changes were observed, including regular financial recording using digital tools, adoption of risk-mitigation strategies, and the establishment of informal community groups led by emerging local leaders. These outcomes reflect not only individual improvements but also broader social transformation within the MSME community.